2021
DOI: 10.1029/2020jd033623
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐Scale, Sector‐Specific Evaluation of Global CO2 Inversion Models Using Aircraft Data From the ACT‐America Project

Abstract: To mitigate the effects of climate change due to greenhouse gases (GHGs), it is vital that we understand the exchange of CO 2 between the atmosphere, biosphere, and ocean, and how these exchanges might vary with time. Previous studies have shown that the land biosphere is a substantial sink of atmospheric CO 2 at present (e.g., Ballantyne et al., 2012; Denning et al., 1995; Gurney et al., 2004; Tans et al., 1990), but much remains unknown about its precise magnitude and long-term trajectory, what accounts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…These intensive, weather-oriented measurements, alongside multi-model simulations from the most recent OCO-2 MIP (version 9), provide us with a new opportunity to better diagnose and quantify the impacts of atmospheric transport uncertainties on spatial distributions of [CO 2 ] in global models and on estimated fluxes. Recently, Gaudet et al (2021) compared OCO-2 MIP inversions constrained with in situ measurements (IS inversions, version 7) against vertical [CO 2 ] profiles in the 2016 ACT-America campaign. They suggested that the OCO-2 MIP members underestimate the differences between the warm and cold sectors of cyclones and have a large model spread in sector-mean [CO 2 ] (>5 ppm) which might be due to differences in inversion systems and/or prior fluxes among models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intensive, weather-oriented measurements, alongside multi-model simulations from the most recent OCO-2 MIP (version 9), provide us with a new opportunity to better diagnose and quantify the impacts of atmospheric transport uncertainties on spatial distributions of [CO 2 ] in global models and on estimated fluxes. Recently, Gaudet et al (2021) compared OCO-2 MIP inversions constrained with in situ measurements (IS inversions, version 7) against vertical [CO 2 ] profiles in the 2016 ACT-America campaign. They suggested that the OCO-2 MIP members underestimate the differences between the warm and cold sectors of cyclones and have a large model spread in sector-mean [CO 2 ] (>5 ppm) which might be due to differences in inversion systems and/or prior fluxes among models.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gaudet et al. (2021) compared OCO‐2 MIP inversions constrained with in situ measurements (IS inversions, version 7) against vertical [CO 2 ] profiles in the 2016 ACT‐America campaign. They suggested that the OCO‐2 MIP members underestimate the differences between the warm and cold sectors of cyclones and have a large model spread in sector‐mean [CO 2 ] (>5 ppm) which might be due to differences in inversion systems and/or prior fluxes among models.…”
Section: Introductionmentioning
confidence: 99%
“…Gaudet et al. ( 2020 ), for example, evaluated the skill of 10 global CO 2 inversion models from the OCO‐2 MIP using 148 airborne vertical profiles of CO 2 for frontal cases from the ACT‐America Summer 2016 campaign. High‐resolution models (Hu et al., 2021 ; Samaddar et al., 2021 ) of the elevated CO 2 band observed along the frontal boundary shown in Pal et al.…”
Section: Applications Of Act‐america Datamentioning
confidence: 99%